Analisis Sistem Kendali Laju Aliran Fresh Water pada Industri Pulp dan Papper Proses Cooker di PT. XYZ - Fauzan Adityo; Arnisa Stefanie (Universitas Pamulang, Prodi teknik Elektro, 2024)
This research focuses on the analysis of the flow rate control system of fresh water in the pulp and paper industry, specifically in the cooker process at PT. XYZ. The control system used involves feedback to ensure the consistency and quality of the final product. By utilizing a Distributed Control System (DCS), this study examines the closed-loop diagram, process flow, DCS programming, and the actual performance data of the fresh water flow rate control system. The results indicate that the control system effectively regulates the fresh water flow rate to achieve the desired viscosity in starch production. Although there is a slight deviation between the set point and the measured instrument reading, the resulting error remains within acceptable tolerances.